2012
DOI: 10.1097/brs.0b013e318226abf7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Compensation and Medical Costs of Lumbar Fusion Patients Receiving Workersʼ Compensation in Utah Using Presurgical Biopsychosocial Variables

Abstract: Medical costs among compensated Utah patients receiving lumbar fusion have risen dramatically since the 1990s, whereas compensation costs have not. Biopsychosocial variables continue to be predictive of these costs, although to a more modest degree than in prior studies. Further investigations should look at other factors leading to increased medical costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This may reflect the higher amounts paid for workers’ compensation claims, for which providers are reimbursed up to 150 % of the AMA listed fees, which are in turn higher than the government-subsidized fees listed in the Australian Medical Benefits Schedule. Lumbar fusion costs rose to AUD 81,297 at 24 months, which is lower than data from the US at USD 72,000 to 90,000 [ 11 , 22 ]. A cervical fusion cost AUD 37,291 in this study compared to USD 42,401 in the US, the latter of which included physiotherapy costs [ 23 ].…”
Section: Discussionmentioning
confidence: 84%
“…This may reflect the higher amounts paid for workers’ compensation claims, for which providers are reimbursed up to 150 % of the AMA listed fees, which are in turn higher than the government-subsidized fees listed in the Australian Medical Benefits Schedule. Lumbar fusion costs rose to AUD 81,297 at 24 months, which is lower than data from the US at USD 72,000 to 90,000 [ 11 , 22 ]. A cervical fusion cost AUD 37,291 in this study compared to USD 42,401 in the US, the latter of which included physiotherapy costs [ 23 ].…”
Section: Discussionmentioning
confidence: 84%
“…6,8,[11][12][13][14][15][16][17] Relatively few studies have evaluated the risk factors for worse outcomes within this clinically distinct population. 6,9,12,13,20,21 Among the 1037 subjects identified in the Ohio Workers' Compensation database who underwent diskogenic fusion, the authors identified a number of preoperative factors that predicted postoperative return to work status. The strongest negative predictor of return to work status was a history of a psychiatric disorder before fusion, with an associated return to work rate of only 2.0%.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even though workers' compensation is a welldescribed risk factor for worse outcomes, relatively few studies have evaluated this population for predictors of worse outcomes. 6,9,12,13,20,21 Among those receiving workers' compensation, the ability to return to work is of particular clinical importance, especially when considering that the estimated cost of treating chronic low back pain is greater than $100 billion per year in the United States, and two-thirds of this cost is believed to result from lost wages and reduced productivity. 22,23 Therefore, the authors wanted to identify preoperative factors that predicted return to work status after diskogenic lumbar fusion in patients with workers' compensation claims.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Few studies have identified prognostic factors within this clinically distinct population. 6,12,14,18,19 The current study was the first to do so among patients with workers' compensation claims who underwent arthrodesis for spondylolisthesis. Among 686 subjects who had workers' compensation claims in Ohio and underwent lumbar fusion for spondylolisthesis from 1993 to 2013, the authors identified a number of preoperative prognostic factors for postoperative return to work.…”
Section: Discussionmentioning
confidence: 98%
“…However, relatively few studies have evaluated potential risk factors for poor outcomes after lumbar fusion among those receiving workers' compensation. 6,12,14,18,19 Therefore, the goal of this study was to identify prognostic factors for return to work status after lumbar fusion for spondylolisthesis within a workers' compensation setting. To the authors' knowledge, this is the first study to identify predictors of return to work specifically among patients with workers' compensation claims who underwent arthrodesis for spondylolisthesis.…”
mentioning
confidence: 99%